SUBSISTENSI BUDAYA: STRATEGI SURVIVAL MASYARAKAT TERDAMPAK KEBIJAKAN SOCIAL DISTANCING DI PERBATASAN INDONESIA-MALAYSIA - Pabali Musa; Adi Suryadi; Rizqi Ratna Paramitha (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
This research is intended to reveal the survival strategy of communities affected by the social distancing policy in border areas, especially Sambas Regency. The study was conducted using qualitative method, and field data collection with interviews and field observations (observations). The goal was to be able to explain the object of research intensively and precisely, namely the survival strategy taken by people on Sambas region border in facing pandemic, especially with their local culture. The subjects of research were Sambas people, especially workers, both local and migrant workers, as well as several related stakeholders. The results of study indicate that the survival strategy taken is a subsistence approach, generally manifested into: (1) subsistence bonds, in the form of forming and maintaining communal cohesiveness and kinship, (2) subsistence ethics, which is strengthening helpful behavior or solidarity, and (3) subsistence production in the form of productivity in the consumptive sector, the result of which is for their own use.